Efficient Production of Pyruvate Using Metabolically Engineered Lactococcus lactis - Suo, Fan; Liu, Jianming; Chen, Jun; Li, Xuanji; Solem, Christian; Jensen, Peter R. (Frontiers in Bioengineering and Biotechnology, 2021)
Microbial production of commodity chemicals has gained increasing attention and most of the focus has been on reducing the production cost. Selecting a suitable microorganism, which can grow rapidly on cheap feedstocks, is of key importance when developing an economically feasible bioprocess. We chose Lactococcus lactis, a well-characterized lactic acid bacterium, as our microbial host to produce pyruvate, which is a commodity chemical with various important applications. Here we report the engineering of Lactococcus lactis into becoming an efficient microbial platform for producing pyruvate. The strain obtained, FS1076 (MG1363 Δ3ldh Δpta ΔadhE Δals), was able to produce pyruvate as the sole product. Since all the competitive pathways had been knocked out, we achieved growth-coupled production of pyruvate with high yield. More than eighty percent of the carbon flux was directed towards pyruvate, and a final titer of 54.6 g/L was obtained using a fed-batch fermentation setup. By introducing lactose catabolism into FS1076, we obtained the strain FS1080, which was able to generate pyruvate from lactose. We then demonstrated the potential of FS1080 for valorizing lactose contained in dairy side-streams, by achieving a high titer (40.1 g/L) and high yield (78.6%) of pyruvate using residual whey permeate (RWP) as substrate. The results obtained, show that the L. lactis platform is well-suited for transforming lactose in dairy waste into food-grade pyruvate, and the yields obtained are the highest reported in the literature. These results demonstrate that it is possible to achieve sustainable bioconversion of waste products from the dairy industry (RWP) to valuable products.